Bglbrick strategy for the construction of single domain antibody fusions. Issue 12 (December 2017) - Goldman, Ellen R.; Broussard, Aeris; Anderson, George P.; Liu, Jinny L.
Abstract: Single domain antibodies, recombinantly expressed variable domains derived from camelid heavy chain antibodies, are often expressed as multimers for detection and therapeutic applications. Constructs in which several single domain antibodies are genetically fused serially, as well as those in which single domain antibodies are genetically linked with domains that naturally form multimers, yield improvement in apparent binding affinity due to avidity. Here, using a single domain antibody that binds envelope protein from the Dengue virus, we demonstrated the construction of single domain antibody dimers using the Bglbrick cloning strategy. Constructing single domain antibodies and multimerization domains as Bglbrick parts enables the easy mixing and matching of parts. The dimeric constructs provided enhanced fluorescent signal in assays for detection of Dengue virus like particles over the monomeric single domain antibody.